Introduction to Logic and Critical Thinking - Van Cleave, Matthew; Open Textbook Library (Open Textbook Library, 2016)
This is an introductory textbook in logic and critical thinking. The goal of thetextbook is to provide the reader with a set of tools and skills that will enablethem to identify and evaluate arguments. The book is intended for anintroductory course that covers both formal and informal logic. As such, it is nota formal logic textbook, but is closer to what one would find marketed as a"critical thinking textbook."
Chapter 1: Reconstructing and analyzing arguments -- 1.1 What is an argument? -- 1.2 Identifying arguments -- 1.3 Arguments vs. explanations -- 1.4 More complex argument structures -- 1.5 Using your own paraphrases of premises and conclusions to reconstruct arguments in standard form -- 1.6 Validity -- 1.7 Soundness -- 1.8 Deductive vs. inductive arguments -- 1.9 Arguments with missing premises -- 1.10 Assuring, guarding, and discounting -- 1.11 Evaluative language -- 1.12 Evaluating a real-life argument -- Chapter 2: Formal methods of evaluating arguments -- 2.1 What is a formal method of evaluation and why do we need them? -- 2.2 Propositional logic and the four basic truth functional connectives -- 2.3 Negation and disjunction -- 2.4 Using parentheses to translate complex sentences -- 2.5 "Not both" and "neither nor" -- 2.6 The truth table test of validity -- 2.7 Conditionals -- 2.8 "Unless" -- 2.9 Material equivalence -- 2.10 Tautologies, contradictions, and contingent statements -- 2.11 Proofs and the 8 valid forms of inference -- 2.12 How to construct proofs -- 2.13 Short review of propositional logic -- 2.14 Categorical logic -- 2.15 The Venn test of validity for immediate categorical inferences -- 2.16 Universal statements and existential commitment -- 2.17 Venn validity for categorical syllogisms -- Chapter 3: Evaluating inductive arguments and probabilistic and statistical fallacies -- 3.1 Inductive arguments and statistical generalizations -- 3.2 Inference to the best explanation and the seven explanatory virtues -- 3.3 Analogical arguments -- 3.4 Causal arguments -- 3.5 Probability -- 3.6 The conjunction fallacy -- 3.7 The base rate fallacy -- 3.8 The small numbers fallacy -- 3.9 Regression to the mean fallacy -- 3.10 Gambler's fallacy -- Chapter 4: Informal fallacies -- 4.1 Formal vs. informal fallacies -- 4.1.1 Composition fallacy -- 4.1.2 Division fallacy -- 4.1.3 Begging the question fallacy -- 4.1.4 False dichotomy -- 4.1.5 Equivocation -- 4.2 Slippery slope fallacies -- 4.2.1 Conceptual slippery slope -- 4.2.2 Causal slippery slope -- 4.3 Fallacies of relevance -- 4.3.1 Ad hominem -- 4.3.2 Straw man -- 4.3.3 Tu quoque -- 4.3.4 Genetic -- 4.3.5 Appeal to consequences -- 4.3.6 Appeal to authority -- Answers to exercisesGlossary/Index
In English.
Description based on online resource
Keywords: Humanities -- Textbooks; Philosophy -- Textbooks